Development of parenteral nanoemulsion systems loaded with carbamazepine for efficient blood-brain barrier crossing in epilepsy treatment - Tan, Sim Ling (2016)
Epilepsy is a neurological disorder characterised by epileptic seizures. Antiepileptic drug is commonly used to reduce the frequency and severity of this disease. Carbamazepine is an effective antiepileptic drug, however, it is limited by the side effects. In addition to the aforementioned problem, carbamazepine delivery to the brain is also, impeded by a biological barrier, the blood-brain barrier. The unique transport-barrier property of the blood-brain barrier further reduces the bioavailability of carbamazepine to the brain. Last but not least, carbamazepine is only available in oral form. To date, parenteral formulation of carbamazepine in not available. In the present study, carbamazepine-loaded, brain targeting parenteral nanoemulsions were developed to overcome these shortcomings. Polyunsaturated fatty acids-rich plant oils such as safflower seed oil, pine nut oil and oleic acid were used in nanoemulsion formulations. Optimisation, characterisation and stability evaluation were carried out to ensure these nanoemulsions meet the requirements of parenteral formulations. The particle size of these nanoemulsions were 119.7 ± 0.90 and 113.97 ± 0.72 nm respectively, the zeta potential were -60.50 ± 1.7 and -58.33 ± 0.58 mV respectively and the polydispersity index were 0.20 ± 0.01 and 0.21 ± 0.01 respectively. Carbamazepine-loaded safflower seed oil nanoemulsion and carbamazepine-loaded pine nut oil nanoemulsion were developed in this experiment and they were subjected to in vitro and in vivo studies. In vitro blood-brain barrier model was developed to determine the penetration efficiency of formulated nanoemulsions. Immortalised cerebral brain endothelial cell lines, hCMEC/D3 and astrocytes (CC-2565) were used to develop co-cultivation in vitro BBB model. Optimisation and characterisation were carried out to ensure the validity of this model. The in vitro study showed that these formulated nanoemulsions possessed higher apparent permeability (0.03 ± 0.01 and 0.05 ± 0.01 cm/h) when compared to carbamazepine solution (0.02 ± 0.001 cm/h). These formulations were also intraperitoneally injected in rats. In vivo pharmacokinetic profiles were generated in this experiment. According to the in vivo study, these formulated nanoemulsions successfully enhanced the plasma (11.20 ± 0.10 and 13.20 ± 0.30 vs. 10.20 ± 0.10 μg/mL) and brain concentrations of carbamazepine (4.10 ± 0.20 and 7.30 ± 0.30 vs. 2.50 ± 0.30 μg/g) when compared to carbamazepine solution. According to the results obtained, drug-loaded nanoemulsions could be an effective carrier for drug transport into the brain. In summary, carbamazepine-loaded, parenteral nanoemulsions have successfully developed and they can markedly increase the level of carbamazepine after intraperitoneal administration in both plasma and brain.